2017
DOI: 10.4103/0972-9941.181776
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus percutaneous endoscopic gastrostomy placement in children: Results of a systematic review and meta-analysis

Abstract: BACKGROUND:Percutaneous endoscopic gastrostomy (PEG) and laparoscopic-assisted gastrostomy (LAG) are widely used in the paediatric population. The aim of this study was to determine which one of the two procedures is the most effective and safe method.METHODS:This systematic review was conducted according to the preferred reporting items for systematic reviews and meta-analyses statement. Primary outcomes were success rate, efficacy of feeding, quality of life, gastroesophageal reflux and post-operative compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Another support of LAG prior PEG regarding complications has also been shown in a previous review of complications after gastrostomy placements [23] and a recent meta-analysis with fewer studies [24]. …”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Another support of LAG prior PEG regarding complications has also been shown in a previous review of complications after gastrostomy placements [23] and a recent meta-analysis with fewer studies [24]. …”
Section: Discussionmentioning
confidence: 70%
“…In a previous meta-analysis on gastrostomy placement in children, using death or reoperations within the first postoperative year as the end points, Baker et al [ 2 ] have also found that the LAG technique was more favorable compared with the PEG technique, with a calculated OR of 0.29 and a 95% CI of 0.17–0.51 ( p = 0.0001), and 45 cases were needed for treatment to reduce one major complication by abandoning PEG placement. Another support of LAG prior PEG regarding complications has also been shown in a previous review of complications after gastrostomy placements [ 23 ] and a recent meta-analysis with fewer studies [ 24 ].…”
Section: Discussionmentioning
confidence: 70%
“…The first review of 22 studies with a total of 5438 patients found a significantly increased risk of major complications with PEG compared to laparoscopic gastrostomy mostly due to a difference in visceral injury between the two techniques [3]. Another recent systematic review and meta-analysis including five retrospective studies found that while completion rates and minor complications were similar between the 550 PEG placements and 483 laparoscopic gastrostomy placements examined, significantly more bowel injuries, early tube dislodgements, and complications requiring reintervention under general anesthesia occurred after PEG placement [4]. Finally, the most recent systematic review confirmed these findings, showing that in a total of eight studies examining 1550 patients undergoing gastrostomy placement, the odds of major complications were more than three-fold higher with PEG (5.4%) compared to laparoscopic gastrostomy (1.0%) [2].…”
Section: Discussionmentioning
confidence: 99%
“…PEG is now well established as an effective method of gastrostomy placement in children and adults after its initial description by Gauderer in 1980 [1]. While some studies have shown similar safety between PEG and SG in children, several meta-analyses have recently reported a higher rate of complications with PEG [2][3][4]. These safety concerns have been most pronounced among the youngest patients [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…2 Similar results were reported in a heterogeneous group of patients. 3 However, PEG showed no differences in mortality or infection compared with percutaneous radiologic gastrostomy. 4 Complications are inherent with any procedure; awareness of immediate and late complications of PEG insertion is vital.…”
mentioning
confidence: 94%